HOMOGENITAS VERSUS MULTIKULTURALISME: PERDEBATAN PENERIMAAN PEKERJA ASING DI JEPANG - Edy Hariyadi (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2012)
This article describes the rivalry of homogenity and multiculturalism conceptions in the debate on acceptance of foreign workers, including fromMuslim world, in Japan. National debate in Japan spawned two opposinggroups, i.e. sakoku group (who reject foreign workers) and kaikoku group(who receive foreign workers). On behalf of the control and power, Japan